Little busters! Season one, Collection 2, Episodes 14-29 [videorecording (DVD)] - Yamakawa, Yoshiki; Kanna, Nobutoshi (Sentai Filmworks, 2014)
As if receiving enigmatic messages delivered by the cats wasn't odd enough, Riki Naoe's world continues to grow even stranger. Following the shocking twin revelations of Midori's missing shadow and the fact that he's the only one who seems to remember Mio, Riki is determined to piece together the puzzle behind their connection. Meanwhile, the dark secrets Haruka is keeping about her family are revealed with potentially devastating consequences, and Riki finds himself pressed into a completely unexpected situation when a sleepover held by Rin and the other female team members goes out of control. However, as overwhelming as all that seems, it's merely the preamble to the drama that's unleashed when Kudryavka learns that her cosmonaut mother is going to be sent into space! And if they didn't have enough on their plate already, the little buster's first ballgame is rapidly approaching as they scramble to find a ninth player. Covert missions are executed, long simmering personal rivalries come to boil, and events that are literally out of this world will take an entire country by storm.